Language Maintenance and Language Shift: A Study on the Rohingya Refugees in Bangladesh - Neloy, Nowshad Hasan (Journal of English Language Teaching and Cultural Studies, 2025)
This study aims at investigating the language situation within the Rohingya refugee community, a marginalized and displaced population originating from Myanmar, in Bangladesh. This study attempts to explore their attitudes towards their mother tongue as well as Bengali. In addition, this study focuses on the native Rohingya speakers and aims to shed light on the factors influencing the preservation or alteration of their mother tongue in this context. A survey was conducted in order to investigate the related issues. The researcher focused on Kutupalong and Balukhali refugee camps in Cox’s Bazar where Rohingya refugees live mostly. Data were collected from randomly selected 90 participants of different age, gender and educational background. Questionnaire and semi-structured interview tools were employed to collect data. Through a combination of qualitative and quantitative research methods, this study examined the linguistic choices, preferences, and practices of the Rohingya refugees in their new host environment. Findings from this study showed that Rohingya refugees have positive attitude towards their mother tongue. Yet, they are gradually shifting from Rohingya to Bengali.